Pengaruh Kompetensi dan Kepemimpinan Terhadap Kinerja Karyawan PT. Pertamina Drilling Services Project Sumatera Bagian Selatan Dengan Motivasi Sebagai Variabel Intervening - Wasis Dwi Atmojo; Trisniarty Trisniarty; Diah Isnaini Asiati (Jurnal Indonesia Sosial Sains, 2022)
This study aims to determine the effect of competence and leadership on employee performance of PT Pertamina Drilling Services Project South Sumatra with motivation as an intervening variable. The type of research conducted is associative with the variables used competence, leadership, motivation and performance which are overall developed into 14 indicators. The population is employees of PT Pertamina Drilling Services Project South Sumatra with 145 respondents taken with probability sampling technique with cluster sampling system. The data used are primary data with questionnaire data collection methods and secondary data taken through the literature. The analysis technique used by researchers is structural equation modeling (SEM) using the SmartPLS 2.0 program. The results of the study prove that: 1) Competence has a positive and significant effect on motivation; 2) Leadership has a positive and significant effect on motivation; 3) Competence has a positive and insignificant effect on performance; 4) Leadership has a positive and significant effect on performance; 5) Motivation has a positive and significant effect on performance. Based on the results of the discussion, it also proves that motivation succeeds in strengthening the influence of competence and leadership on performance.